Effectiveness of self-regulated learning intervention on foreign language learning at tertiary level: a systematic review - Su, Li; Noordin, Nooreen; Jeyaraj, Joanna Joseph (Sciedu Press, 2023)
Self-regulated learning (SRL) has been widely recognized as an efficient way of enhancing foreign language learning (FLL) outcomes in the sphere of higher education. The current study aimed to evaluate the effectiveness of SRL interventions or supports in improving foreign language learning among learners in tertiary institutions. The review involved 20 studies pertaining to exploring the effects of SRL interventions on improving FLL. According to this systematic review, SRL interventions can be successful in improving various aspects of FLL, including language proficiency, language learning strategies (LLS), motivation, and self-efficacy. The review also provides practical implications for language practitioners and researchers, including the need to tailor SRL interventions to the specific specialized demands of EFL learners and the importance of considering contextual factors to devise and administer SRL interventions in the sphere of FLL at tertiary education. However, several limitations of the existing studies are also identified, including limited assessment of long-term effects, limited use of control groups, insufficient consideration of individual differences, and lack of use of the mixed-methods approach. The findings also provide implications for future studies to address these limitations and provide a more nuanced understanding of the effectiveness of SRL interventions on foreign language learners. Specifically, future studies should incorporate longer-term assessments, stronger control groups, assessments of individual differences, and the mixed-methods approach. Overall, the paper provides insights into the strengths and limitations of existing research and highlights areas for future inquiry concerning SRL and foreign language acquisition.